PENGUATAN BRANDING KAMPUNG WARNA-WARNI JODIPAN MELALUI DESAIN IDENTITAS VISUAL KAWASAN - Mariana; Cyntya Febrianti; Bernanto Aditya Kosasih; Avrello Alsando (Jurnal Bakti Masyarakat Indonesia, 2026)
Jodipan Tourism Village in Malang City is one example of the successful transformation of a slum area into a thematic tourist destination with high visual appeal. Through its distinctive colorful concept, Jodipan has succeeded in attracting the attention of domestic and international tourists and has become an icon of creative tourism in Malang City. However, with the increasing number of similar tourist destinations, new challenges have emerged for Jodipan Village: maintaining its existence and positive image amidst increasingly competitive tourism competition. This condition demands a strengthened visual communication strategy that is more focused through the design of a visual identity that is able to represent local cultural values, unique character, and tourism potential of the area. This community service activity was carried out using qualitative methods that included direct observation, interviews with residents and tourism managers, and field research to understand the social, cultural, and visual context of Jodipan Village. The main objective of this activity was to design a visual identity system that would serve as an effective communication and promotional medium, both in print and digital media. This design is expected to strengthen the professional image of Jodipan Village as a creative, community-based tourism destination, while increasing its visual appeal for tourists. Through a participatory process, the Jodipan community was also encouraged to be actively involved in maintaining and developing the designed visual identity, thereby fostering a sense of ownership and pride in their tourism village. Thus, this activity not only contributes to increasing tourism appeal and the local economy but also strengthens the sustainability of community-based tourism thai is aligned with the objectives of the Sustainable Develompment Goals (SDGs), especially SDG 11: Sustainable Cities and Communities. ABSTRAK Kampung Wisata Jodipan di Kota Malang merupakan salah satu contoh keberhasilan transformasi kawasan permukiman kumuh menjadi destinasi wisata tematik yang memiliki daya tarik visual tinggi. Melalui konsep warna-warni yang khas, Jodipan berhasil menarik perhatian wisatawan domestik maupun mancanegara dan menjadi ikon wisata kreatif Kota Malang. Namun, seiring meningkatnya jumlah destinasi wisata serupa, muncul tantangan baru bagi Kampung Jodipan untuk mempertahankan eksistensi dan citra positifnya di tengah persaingan pariwisata yang semakin kompetitif. Kondisi ini menuntut adanya penguatan strategi komunikasi visual yang lebih terarah melalui perancangan identitas visual yang mampu merepresentasikan nilai-nilai budaya lokal, karakter unik, serta potensi wisata yang dimiliki kawasan tersebut. Kegiatan pengabdian masyarakat ini dilaksanakan dengan metode kualitatif yang meliputi observasi langsung, wawancara dengan warga dan pengelola wisata, serta riset lapangan untuk memahami konteks sosial, budaya, dan visual Kampung Jodipan. Tujuan utama kegiatan ini adalah merancang sistem identitas visual yang berfungsi sebagai media komunikasi dan promosi yang efektif, baik pada media cetak maupun digital. Perancangan ini diharapkan dapat memperkuat citra profesional Kampung Jodipan sebagai destinasi wisata kreatif berbasis komunitas, sekaligus meningkatkan daya tarik visual bagi wisatawan. Melalui proses partisipatif, masyarakat Jodipan juga didorong untuk terlibat aktif dalam menjaga dan mengembangkan identitas visual yang telah dirancang, sehingga terbentuk rasa memiliki dan kebanggaan terhadap kampung wisata mereka. Dengan demikian, kegiatan ini tidak hanya berkontribusi pada peningkatan daya tarik wisata dan ekonomi lokal, tetapi juga memperkuat keberlanjutan pariwisata berbasis pemberdayaan masyarakat yang selaras dengan tujuan Sustainable Development Goals (SDGs), khususnya SDG 11: Sustainable Cities and Communities.